Komunikasi Preventif Radikalisme Agama pada Mahasiswa di Perguruan Tinggi Kota Ambon - Hakis Hakis (Jurnal Ilmu Komunikasi, 2020)
This article discusses how religious radicalism preventive communication among students at University of Ambon. This type of research is a qualitative descriptive with a phenomenological approach to investigate social and religious phenomena in university students. The findings of preventive communication in counteracting religious radicalism in Higher Education are: the communication of the campus academics has not been maximized to students in fostering religious understanding. Every tertiary institution needs to have real student data starting from data on their religious understanding so that they know students who are exposed to religious radicalism. The campus is expected to prepare tutor facilities in communicating preventively about religious radicalism and the dangers it causes.